Participatory action research for changing gender norms and achieving women’s and youth’s empowerment in mixed barley-livestock systems in Ethiopia - Najjar, Dina; Tsige, Meseret; M. Oumer, Ali; Frija, Aymen; Ekule, Muluken; Wamatu, Jane; Haile, Aynalem; Sanchez-Garcia, Miguel (International Center for Agricultural Research in the Dry Areas, 2024)
Far less attention is given to the social domains of Sustainable Intensification (SI). However, to intensify agricultural production sustainably, technical solutions must be paired with the social, economic and political innovations that can support their adoption by smallholder farmers (Barrett et al. 2020; Cook et al. 2015; Kuyah et al. 2021). The need for better understanding of broader contextual issues to enable the realization of pathways forward to improve SI adoption is often reiterated as a gap in theoretical and applied assessment literature. We employ participatory action research that focuses on bundling of social and technical aspects with regards to sheep fattening and improved barley varieties. We focus on social networks and institutions that affect access to knowledge and key farming resources and take an intersectional approach to gender. We work with producers, private companies, consumers, processors (many of whom are landless women), breeders, sellers and traders to enable access to better varieties and breeds and more sustainable practices. We focus on collective action for enabling access to information, inputs, essential networks and overcoming harmful social norms.